Diagnostic significance of the determination of antinuclear antibodies in children with autoimmune hepatitis - A. A. Zhuzhula; O. V. Kurbatova; S. V. Petrichuk; D. V. Parakhina; M. A. Snovskaya; G. B. Movsisyan; E. L. Semikina; A. S. Potapov; A. P. Fisenko (Аллергология и Иммунология в Педиатрии)
.